CONSTRUCTION OF OPTIMAL PORTFOLIO JAKARTA ISLAMIC STOCKS USING SINGLE INDEX MODEL TO STOCKS INVESTMENT DECISION MAKING - Agus Setyo, Tri; Abitur Asianto; Augustina Kurniasih (Dinasti Publisher, 2020)
This study aims to determine and analyze the optimal portfolio forming stocks using the Single Index Model, determine the optimal portfolio risk and return expectations, then compare the optimal portfolio risk and return expectations with market return expectations, then analyze the optimal portfolio performance using the Treynor model. The research was conducted on the Jakarta Islamic Index stocks. Population of 48 issuers, which meet the sample criteria of 14 issuers. Using monthly data for the period December 2014-November 2019, it was found that 2 stocks entered the optimal portfolio, namely (with a proportion of funds) ICBP (91.46%) and TLKM (8.54%). The value of E (Rp) 0.0128 is greater than the value of E (RM) 0.0003 and the value of the risk free rate is 0.0048. The value of ?p 0.0438 is greater than the value of ?2M 0.0364. The value of portfolio performance with the Treynor index is 0.0091.